Endoscopic submucosal dissection for early Barrett's neoplasia. Issue 2 (April 2016) - Barret, Maximilien; Cao, Dalhia Thao; Beuvon, Frédéric; Leblanc, Sarah; Terris, Benoit; Camus, Marine; Coriat, Romain; Chaussade, Stanislas; Prat, Frédéric
Introduction: The possible benefit of endoscopic submucosal dissection (ESD) for early neoplasia arising in Barrett's esophagus remains controversial. We aimed to assess the efficacy and safety of ESD for the treatment of early Barrett's neoplasia. Methods: All consecutive patients undergoing ESD for the resection of a visible lesion in a Barrett's esophagus, either suspicious of submucosal infiltration or exceeding 10 mm in size, between February 2012 and January 2015 were prospectively included. The primary endpoint was the rate of curative resection of carcinoma, defined as histologically complete resection of adenocarcinomas without poor histoprognostic factors. Results: Thirty-five patients (36 lesions) with a mean age of 66.2 ± 12 years, a mean ASA score of 2.1 ± 0.7, and a mean C4M6 Barrett's segment were included. The mean procedure time was 191 ± 79 mn, and the mean size of the resected specimen was 51.3 ± 23 mm. En bloc resection rate was 89%. Lesions were 12 ± 15 mm in size, and 81% (29/36) were invasive adenocarcinomas, six of which with submucosal invasion. Although R0 resection of carcinoma was 72.4%, the curative resection rate was 66% (19/29). After a mean follow-up of 12.9 ± 9 months, 16 (45.7%) patients had required additional treatment, among whom nine underwent surgical resection, and seven further endoscopic treatments. Metachronous lesions or recurrence of cancer developed during the follow-up period in 17.2% of the patients. The overall complication rate was 16.7%, including 8.3% perforations, all conservatively managed, and no bleeding. The 30-day mortality was 0%. Conclusion: In this early experience, ESD yielded a moderate curative resection rate in Barrett's neoplasia. At present, improvements are needed if ESD is to replace piecemeal endoscopic mucosal resection in the management of Barrett's neoplasia.